PEMANFAATAN LAHAN SEKITAR EMBUNG UNTUK KAJIAN BUDIDAYA BAWANG MERAH - Forita Dyah Arianti; Suprapto Suprapto; Sodik Jauhari; Eman Supratman (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Changes in precipitation patterns, increase in frequency of extreme climate events, and rise in temperatures and sea level were serious impacts of climate change faced by Indonesia. Agriculture is the most vulnerable sector influenced by of the climate change. In the current condition, optimizinyon natural resource utilization is one of ways to recover economic condition of farmers. The use of reservoir on dry land aimed to conservation water resource and restrain erosion rate is the best cheap and efficient solution. Then, water retained can be used for agriculture in dry season. This rain water harvesting is suitable for rainfed ecosystem which has uncertain intensity and distribution of rainfall. This study aimed to identify the production of onion cultivated in dry area around reservoirs, to give alternative farming around reservoir in order to increase income for farmer. The study was conducted in Getas village of Kradenan district, and Randublatung village of Randublatung district in Blora regency. The Result of this study indicated that the average onion production in Getas village and Randublatung village was 10.33 t/ha and 11.63 t/ha with R/C ratio of 1.45 and 1.59, respectively. The farmers very strong motivation could support the successful implementation of new plant cultivation although their level of knowledge and experience also influenced the successful farming . Farmer perception on onion cultivation technology on land araund reservoir was very positive